ANALISIS YURIDIS ATAS PENGENAAN PAJAK PENGHASILAN (PPh) FINAL ATAS PERMOHONAN PENDAFTARAN TANAH HIBAH BERDASARKAN PERATURAN PEMERINTAH NOMOR 34 TAHUN 2016 - WILLY SYAHPUTRA L. TOBING (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Dr. Utary Maharany Barus, SH, MHum3. Dr. Bastari, MM An application for registration of rights over the land granted to a first degree relative is submitted because the land and/or building rights are transferred. This case has encouraged a further research entitled “A juridical Analysis of Final Income Taxation for the Application for Registration of Granted Land grounded on the Government Regulation No. 34/2016.” The research problems are how the provisions concerning the authority of National Land Office are stipulated regarding the Final Income Taxation for Land and/or Building Right Transfer in the application for registration of the land granted to a first degree relative, how the legal certainty principle is about the Final Income Taxation for the application for registration of the land granted to a first degree relative, and how the justice principle is fulfilled about the exception in the Final Income Taxation for Land and/or Building Right Transfer in the application for registration of the land granted to a first degree relative. This is a normative juridical research with descriptive analysis. It uses secondary data consisting of primary legal materials such as Law No. 36/2008 on Income Tax and the Government Regulation No. 34/2016 on Land and/or Building Right Transfer made in a Sale and Purchase Contract for the Land and/or Building and any changes on them (PHTB-PPJBTB), secondary legal materials such as books, and tertiary legal materials such as dictionaries.Keywords: Tax, Application for Land registration, Grant